Preservation Effect Of Peg (Polyethylene Glycol) In Sugarcane (Saccharum officinarum) Nxi 1,3 Synthetic Seed - Ningtiyas, Wulan Nursyiam; Dewanti, Parawita; Sugiharto, Bambang (ANNALES BOGORIENSES, 2016)
Encapsulation is a method for embryogenic tissue coating system by Na-alginate which has synthetic seed preservation purpose. To produce sugarcane synthetic seed need Coleoptillar embryogenic callus and apical bud that it is encapsulated by encapsulation media (MS0 + 4% Na-alginat+ 100 mM CaCl2). In this study, PEG (0%, 1%, 2%, 3%) and PBZ (0 ppm, 1 ppm, 2 ppm, 3 ppm) add to media encapsulation which are give desiccation effect (PEG) and Giberellin synthesis blockade system. Both of PEG or PBZ is used to sugarcane synthetic seed growth retardation that it is implied as storage period. The result are show that PEG 2% is the most effective concentration which is added in encapsulation media. Dessiccation effect of PEG 2% can make synthetic seed storage period until 3 weeks, synthetic seed regeneration produce 89,32 planlets and planlets clorophill concentration is 26,03 ????g/mL. PBZ 1 ppm is the most effective concentration to make storage period until 5 weeks, synthetic seed regeneration produce 39 planlets and planlets clorophill concentration is 35,81 ????g/mL.